Comparable anatomical and functional success to younger patients in endoscopic dacryocystorhinostomy patients of older age - Erkan, Erol; Çıkrıkcı, Sercan; Ağdaş, Fatih (Journal of Surgery and Medicine, 2021)
Background/Aim: Endoscopic dacryocystorhinostomy (EDCR) has many advantages over the external method, with comparable anatomical and functional success rates. Delayed wound healing is reported to be associated with older age in previous studies. In this study, we aimed to assess the effect of age on the functional and anatomic success of our EDCR results. Methods: A total of 55 patients with nasolacrimal duct obstruction (NLDO) were included in this retrospective cohort study. Patients were managed with either EDCR alone or EDCR combined with nasal septoplasty in our hospital. The patients were divided into two groups as Group 1 (20-54 years old) and Group 2 (55-77 years old) according to age. Results: The mean ages of the patients in Groups 1 and 2 were 38.53 (9.55) years and 66.24 (6.36) years, respectively (P<0.001). EDCR was performed on 30 nasolacrimal ducts in Group 1 and 38 nasolacrimal ducts in Group 2. Forty-one cases (60.3%) were managed only with EDCR, and 27 (39.7%) patients underwent septoplasty surgery in addition to EDCR due to septum deviation. There was no significant difference between the groups in terms of anatomical and functional success (P=0.239 and P=0.233). Conclusion: Our results showed that comparable anatomical and surgical success rates are possible in NLDO in older patients compared with younger patients. This result may encourage surgeons with question marks about the success of the EDCR in older age NLDO patients.